Pelaksanaan Continuous Quality Improvement (CQI) dalam Kalangan Pensyarah di Kolej Kemahiran Tinggi Mara - Daud, Lyssa; Yunus, Faizal Amin Nur; Rahim, Mohd Bekri; Rozali, Mohd Zulfadli; Abdul Rahman, Khairul Anuar; Kamis, Arasinah (Online Journal for TVET Practitioners, 2020)
Continuous quality improvement, CQI at institutional level is a process of continuously reviewing and updating teaching and learning activities ranging from planning, implementation, monitoring and enhancement processes. A review of the CQI implementation at KKTM found that the implementation of CQI was only at the monitoring level and continuous improvement was not practiced. There are three parties responsible for implementing CQI in an institution such as management, academic staff and students. Therefore, this study is aimed at identifying the level of CQI implementation among KKTM lecturers based on three factors namely knowledge, commitment and empowerment to evaluate whether the implementation on the part of the lecturer which is the cause of this improvement does not occur. The design of this study is a quantitative study through a survey method. Random sampling is easy to use for sample consisting of 132 lecturers from three South KKTM zones, KKTM Sri Gading, KKTM Ledang and KKTM Masjid Tanah. The data were analyzed using SPSS Statistics 22. The findings show that the level of CQI implementation is high in terms of knowledge (3.83), in terms of commitment (3.97), and in terms of mastery (3.76). In addition, the findings from the correlation values also showed a moderate relationship (.63) between knowledge level and commitment to CQI implementation, strong relationship (.70) between knowledge level and mastery of CQI implementation and strong relationship. commitment and input on CQI implementation. Based on the clear data it shows that the level of knowledge, commitment and mastery of the lecturers is good in ensuring the implementation of CQI in KKTM. But some aspects of commitment and management can be enhanced by management strategies and management improvements